Study on the application of modified Baduanjin exercise in accelerating rehabilitation of patients with tuberculosis of lumbar spine (改良八段锦在腰椎结核患者加速康复中的应用研究) - TANG Ling (唐玲); TAN Jiarong (谭佳容); TANG Yang (唐阳); HE Jing (何静); MU Lianghai (穆浪海) (中西医结合护理)
Objective To investigate the effect of modified Baduanjin exercise in accelerated rehabilitation of patients after surgery for tuberculosis of lumbar spine. Methods Totally 66 patients with tuberculosis of lumbar spine were randomly divided into study group and control group. The control group received routine rehabilitation training, and the study group received modified Baduanjin exercise intervention on the basis of routine rehabilitation training. Function Independent Measure(FIM)score, Spinal Cord Independence Measure Ⅲ (SCIMIII) score, Barthel Index (BI)score, Visual Analogue Scale (VAS) score and straight leg raising test were used before intervention and 1 week, 2 weeks and 4 weeks after intervention. Results Scores of FIM、SCIM-Ⅲ and BI increased in both two group at 1, 2 and 4 weeks after intervention, and Scores of FIM、SCIM-Ⅲ and BI in the study group were higher than those in the control group (P＜0. 05). The VAS score of rest pain at affected limb in the study group was lower than that in the control at 1, 2 and 4 weeks after intervention, respectively (P＜0. 05). There was a significant difference in degree of limitation of straight-leg raising between two groups at 1, 2 and 4 weeks after intervention, respectively (P＜0. 05). Conclusion Modified Baduanjin exercise can effectively reduce the postoperative pain, improve lumbar function, improve the quality of daily life and activity of daily living, and promote the neurological function and motor function of patients after surgery for tuberculosis of lumbar spine. (目的 研究改良八段锦在腰椎结核患者加速康复中的应用效果。方法 将66例腰椎结核手术患者随机分为研究组和对照组。对照组采取常规康复训练, 研究组在常规康复训练的基础上接受改良八段锦进行运动干预。分别于干预前及干预后1周、2周和4周采用功能独立性评定(FIM)、脊髓独立性评估量表Ⅲ(SCIM-Ⅲ)评分、Barthel指数评分(BI)、视觉模拟评分(VAS)及直腿抬高试验进行评价分析。结果 干预后1周、干预后2周、干预后4周, 2组患者的FIM、SCIM-Ⅲ和BI评分均较干预前提高(P＜0. 05), 且研究组FIM、SCIM-Ⅲ和BI评分高于对照组, 差异有统计学意义(P＜0. 05)。干预后1周、干预后2周、干预后4周, 研究组患者的患肢静息疼痛 VAS评分均低于对照组, 差异有统计学意义(P＜0. 05)。干预后1周、干预后2周、干预后4周, 2组患者直腿抬高试验角度差异有统计学意义(P＜0. 05)。结论 改良八段锦干预能有效减轻腰椎结核患者术后疼痛, 改善腰椎功能, 提高术后日常生活质量和生活能力, 促进患者神经功能和运动功能。)